Baccilus thuringiensis Effectiveness As Larvasida Malaria Vectors in the District of Batu Layar, West Lombok - Urip Urip; Erlin Yustin Tatontos; Nurul Inayati (Jurnal Riset Kesehatan, 2012)
This research aim to test the effectivity of Baccilus thuringiensis as larvasida malaria vector in Subdistrict Batu Layar of Regency West Lombok, test to involve in laboratory and also in field. Data yielded by LD (Lethal Dose) 50 and LD 90 to test involve and difference sum up the larva of nopheles sp before and hereafter gift of Baccilus thuringiensis. Result of research test to involve in laboratory, Baccilus thuringiensis efektivity used by larvacide malaria vector with the analysis probit at belief storey level 95% LD 50 0,03 ppm and LD 90 0,069 ppm. Result of research test effectivity in field, Baccilus thuringiensis efektiv used as larvacide malaria vector, with the analysis t test there was difference meaning the larva amount of before and hereafter gift of Baccilus thuringiensis that was t = 0,023.